The milliped family Platyrhacidae (Polydesmida: Leptodesmidea) in the West Indies: Proposal of Hoffmanorhacus n. gen.; description and illustrations of males of Proaspis aitia Loomis, 1941; redescription of Nannorrhacus luciae (Pocock, 1894); hypotheses on origins and affinities; and an updated New World familial distribution - Shelley, Rowland M.; Martinez-Torres, Daniela (Zootaxa, 2013)
In the New World, the milliped family Platyrhacidae (Polydesmida) is known or projected for Central Americasouth of southeastern Nicaraguaand the northern ¼ of South America, with disjunct, insular populations on Hispaniola(Haiti), Guadeloupe(Basse-Terre), and St. Lucia. Male near-topotypes enable redescription of Proaspis aitia Loomis, 1941, possibly endemic to the western end of the southern Haitian peninsula. The tibiotarsus of its biramous gonopodal telopodite bends strongly laterad, and the medially directed solenomere arises at midlength proximal to the bend. With a uniramous telopodite, P. sahlii Jeekel, 1980, on Guadeloupe, is not congeneric, and Hoffmanorhacus, n. gen., is erected to accommodate it. Nannorrhacus luciae (Pocock, 1894), onSt. Lucia, is redescribed; also with a biramous telopodite, its tibiotarsus arises distad and diverges from the coaxial solenomere. The Antillean species do not comprise a clade and are only distantly related; rather than introductions, they plausibly reflect ancestral occurrences on the “proto-Antillean” terrain before it rifted from “proto-SouthAmerica” in the Cretaceous/Paleocene, with fragmentation isolating modern forms on their present islands. Existing platyrhacid tribes are formally elevated to subfamilies as this category was omitted from recent taxonomies. Without unequivocal evidence to the contrary, geographically anomalous species should initially be regarded as indigenous rather than anthropochoric.